Contribuições para o estudo da capacitação tecnológica no Brasil: as empresas de base tecnológica e as universidades - Barretto, Antonio Luiz; Pinho, Marcelo; Rocha, Mauro (Revista Gestão da Produção Operações e Sistemas, 2006)
The analysis of a country’s technological learning process depends on the understanding of the involved elements in their innovative environment. The National System of Innovation approach enables the recognition not only of all agents and their interactions, but also of the environment which characterizes the agents and conditions their actions. Considering that the technological capability process is an important element for the development of any country, the main purpose of this article is to work with two agents from the Brazilian technological environment: New Technology-Based Firms and universities, highlighting the spinoff process based on transference of knowledge from universities to spin-off firms and cooperation plans between them. Keywords: National System of Innovation; Spin-off, Universities; New Technology-Based Firms (NTBFs).